Conflict Management Styles Used by Teachers at Public and Private Sector Universities of Lahore - Parveen, Zahida; Iqbal, Javeria; Latif, Zeba (Journal of Applied Research and Multidisciplinary Studies, 2020)
This study aimed to investigate the most prevalent Conflict Management Styles (CMSs) among teachers at public and private sector universities of Lahore. For this purpose, a survey was conducted using Rahim Organizational Conflict Inventory Roci-II form C. This inventory was pilot tested and its reliability was found to be 0.86. The sample comprised 446 teachers selected using two-stage random sampling technique from six public and private sector universities of Lahore. The findings revealed that managing conflicts through accommodating and collaborating styles were practiced by university teachers and these particular styles mostly prevailed among them. There was no meaningful difference found between teachers from public and private universities; however, some differences were found on the basis of other demographic variables such as gender, designation, age, and qualification of respondents.